Targeting extracellular matrix through phytochemicals: a promising approach of multi-step actions on the treatment and prevention of cancer - Liang, Dan; Liu, Lu; Zhao, Yunjie; Luo, Zhenyi; He, Yadi; Li, Yanping; Tang, Shiyun; Tang, Jianyuan; Chen, Nianzhi (Frontiers in Pharmacology, 2023)
1.Based on extensive researches on extracellular matrix (ECM), this review provides a reference for the subsequent research on the mechanism of tumor occurrence and development and the development of new drug targets in the future. 2.Based on the coincidence between the whole-process of tumor progression and the ECM remodeling trilogy, we propose three phases of whole-process management of cancer and the necessity of targeting ECM remodeling trilogy in the treatment of tumors. 3.This paper is the first time comprehensively to summarize the current situation of natural products targeting ECM research, providing more new perspectives and research fields for following researchers. Abstract： Extracellular matrix (ECM) plays a pivotal and dynamic role in the construction of tumor microenvironment (TME), becoming the focus in cancer research and treatment. Multiple cell signaling in ECM remodeling contribute to uncontrolled proliferation, metastasis, immune evasion and drug resistance of cancer. Targeting trilogy of ECM remodeling could be a new strategy during the early-, middle-, advanced-stages of cancer and overcoming drug resistance. Currently nearly 60% of the alternative anticancer drugs are derived from natural products or active ingredients or structural analogs isolated from plants. According to the characteristics of ECM, this manuscript proposes three phases of whole-process management of cancer, including prevention of cancer development in the early stage of cancer (Phase I); prevent the metastasis of tumor in the middle stage of cancer (Phase II); provide a novel method in the use of immunotherapy for advanced cancer (Phase III), and present novel insights on the contribution of natural products use as innovative strategies to exert anticancer effects by targeting components in ECM. Herein, we focus on trilogy of ECM remodeling and the interaction among ECM, cancerassociated fibroblasts (CAFs) and tumor-associated macrophages (TAMs), and sort out the intervention effects of natural products on the ECM and related targets in the tumor progression, provide a reference for the development of new drugs against tumor metastasis and recurrence.